1994
DOI: 10.1159/000310452
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Oncocytoma in the Eyelid

Abstract: Oncocytoma rarely arises from the eyelid and only 2 cases have been reported previously. We present a case of oncocytoma in the upper eyelid around the lacrimal punctum. Anatomical location and histological findings suggested that oncocytes of this tumor originated from the epithelium of Moll’s gland or the lacrimal canaliculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We previously reported a case of oncocytoma of the eye lid [1] and suggested that oncocytes can be divided into co lumnar-type cells that constitute the tubular portion and pol ygonal-type cells that constitute the solid portion of the tu mor. However, the questions of whether there are essential differences between these two cell types and what the essen tial differences are if there are any, remained unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a case of oncocytoma of the eye lid [1] and suggested that oncocytes can be divided into co lumnar-type cells that constitute the tubular portion and pol ygonal-type cells that constitute the solid portion of the tu mor. However, the questions of whether there are essential differences between these two cell types and what the essen tial differences are if there are any, remained unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…They have not attracted much attention because of their rarity [3]. The anatomical location and histological findings of oncocytomas of the peripunctum suggest they originate from the epithelium of Moll's gland or the epithelium of the lacrimal canaliculus [3][4][5][6]. Our findings suggest that oncocytomas of the peripunctum originate from the epithelium of the lacrimal canaliculus, because histopathological examination showed that the lacrimal canaliculus space was entirely replaced by tumor cells and there was no continuity to the skin or conjunctival surface.…”
Section: Discussionmentioning
confidence: 73%
“…Oncocytoma of the peripunctum or eyelid margin is rare. We are aware of four reported cases of peripunctal oncocytoma [3][4][5][6], and four cases of the eyelid margin not involving the peripunctal area [1,[7][8][9]. This distribution was somewhat unexpected, because the area of the eyelid margin is much larger than that of the peripunctum.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors may develop in the lacrimal glands (7), sac (7-10), and the caruncle (7)(8)(9)(11)(12)(13)(14)(15). Some palpebral oncocytomas like this case originate from the epithelium of Moll's gland or from the epithelium of the lacrimal duct (16)(17)(18)(19). In spite of appereance of oncocytes in the lacrimal apparatus, palpebral involvement is a rare site for tumor formation (20).…”
Section: Discussionmentioning
confidence: 97%